Pembinaan Narapidana Gangguan Kejiwaan Pada Lapas Kelas II A Magelang - Zada Aryaguna; Ali Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The development of prisoners has become an obligation carried out in a correctional institution. All correctional inmates should receive this training while serving their sentence in prison. As stated in Law No.12/1995 concerning Correctional Institutions and Government Regulation no. 99 of 2012 concerning the Second Amendment to Government Regulation Number 32 of 1999 concerning Requirements and Procedures for Implementing the Rights of Correctional Inmates, however, it does not explain how to provide guidance for an Inmate who experiences mental disorders. Therefore, it is a big homework for correctional officers, especially prisons, in providing treatment, especially in terms of guidance for prisoners who experience mental disorders. This research aims to determine the treatment and guidance of prisoners who experience mental disorders. This research also reveals that there is no definite policy for ODGJ prisoners to get reduced sentences and early release with consideration of treatment. However, in the Class II A Magelang Penitentiary, full efforts have been made to treat prisoners who experience mental disorders by seeking routine treatment in collaboration with the local mental hospital for efforts to cure prisoners and this is proven by the existence of a prisoner who has recovered from mental disorders thanks to the presence of Efforts are being made by prisons involving mental hospitals so that the treatment and care given is appropriate.